Monetary policy transmission to Russia & Eastern Europe - Carsten M. Stann; Theocharis Grigoriadis (Freie Universität Berlin, School of Business & Economics, 2019)
In this paper, we argue that the ECB's unconventional monetary policy announcements have generated significant spillover effects in Russia and Eastern Europe. The hypothesis is tested using OLS estimations of event-based regressions on monetary policy event dummies and seven financial variables in eleven East European countries including Russia. Overall, the empirical results associate the ECB's unconventional policy announcements with the appreciation of East European currencies, rising stock market indices as well as falling long-term government bond yields and lower sovereign CDS spreads in Eastern Europe and Russia. Notably, bilateral integration with the eurozone is a key determinant of the strength of spillovers, with spillovers strongest in non-euro EU countries and weakest in non-EU East European countries. Interestingly, we find differentiated strength of spillovers to Russia compared to other non-EU East European countries, which we attribute to its fixed exchange rate regime. Lastly, we test for the presence of the portfolio rebalancing and confidence transmission channels.
urn:nbn:de:kobv:188-refubium-24609-8
Keywords: E52; E58; F34; F37; F42; P51; 330; monetary policy transmission; spillovers; European Central Bank; transmission channels; Eastern Europe; Russia